2019
DOI: 10.17756/jrdsas.2019-042
|View full text |Cite
|
Sign up to set email alerts
|

Reward Deficiency Syndrome Solution Focused Brief Therapy to Begin Integrating the Sciences of Addiction & Reward Deficiency Syndrome (RDS)

Abstract: Reward Deficiency Syndrome Solution Focused Brief Therapy (RDS-SFBT), provided in both individual and group therapy formats, in the practice of Addiction Recovery Treatment, will help the client understand the importance of the challenge to achieve dopamine homeostasis in the recovery process. RDS-SFBT introduces new Reward Deficiency Syndrome concepts and solutions to the practitioner-client world, helping to bridge the gap between the worlds of research and therapeutic practice [1]. Newly created RDS-SFBT wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…We have the resources to stop addiction before it begins. The future is now (Blum, Steinberg, Gondre-Lewis, Baron Gilley, 2019) therapies are appropriate, and prescribed as part of the RDS treatment plan protocol (Gilley, 2018e).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have the resources to stop addiction before it begins. The future is now (Blum, Steinberg, Gondre-Lewis, Baron Gilley, 2019) therapies are appropriate, and prescribed as part of the RDS treatment plan protocol (Gilley, 2018e).…”
Section: Discussionmentioning
confidence: 99%
“…Brief Intervention (RDS-SFBI) administers bio-neuro-psychological therapy which assists the client in achieving dopamine homeostasis (Gilley, 2019). Since RDS effects the individual over the entire lifespan, it should be treated as a front-line modality (Blum, Raza, Schultz, Jalali, Green, Brewer, et al 2021), by primary physicians, and teams of RDS specialists (Gilley, Bowirrat, Gupta, Giordano, Dennen, Braverman, Badgaiyan, McLaughin, .…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps new expansive definitions of RDS related Anhedonia and Dysphoria, the resulting volatility and rage that comes with unending undercurrent of stress associated with Anhedonia, need to be developed for RDS psychoeducation of patients, along with Likert Scale measurements for self-report of Anhedonia and Dysphoria experience [6,23]. These may be useful in future development of RDS adapted cognitive behavioral therapy to help inform clients through self-awareness, for self-management techniques for the purpose of achieving dopamine homeostasis to combat relapse and facilitate wellbeing [11].…”
Section: Research Reviewmentioning
confidence: 99%
“…Over fifty years of addiction science and neuro-genetic research have identified a new phenotype for impulsive, compulsive, obsessive and addictive behavioral expression which is changing the recovery landscape by linking all addictions under a common rubric [6][7][8][9][10][11][12][13]. The science of Reward Deficiency Syndrome (RDS) offers hope for SUD and for all obsessive, compulsive, and addictive behavioral patterns.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that pleasure is not a single structure, and in a depressed person, the lack of motivation for reward is primarily due to low levels of anticipation of pleasure rather than a decrease in interest. 6 , 7 Also the importance of studying the reward processes can be illustrated by the fact that in certain conditions, one reward function can be impaired while the others remain intact. For example, individuals with major depression disorder have similar hedonic responses to sweet solutions compared to controls, 8 but are less likely to engage in tasks requiring higher amounts of effort.…”
Section: Introductionmentioning
confidence: 99%